1998
DOI: 10.1046/j.1523-1747.1998.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Sulfate Inhibits Proteases that are Involved in Desquamation of Stratum Corneum

Abstract: We previously reported that desmosomes play a key role in the adhesion of corneocytes, and their digestion by two types of serine proteases leads to desquamation. Patients with recessive X-linked ichthyosis show hyperkeratosis attributable to desmosomes, associated with an increased content of cholesterol sulfate (CS) and an increased thickness of stratum corneum. In this study, therefore, we examined the possibility that CS provokes the abnormal desquamation, acting as a protease inhibitor. Scaling was induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 17 publications
0
77
0
Order By: Relevance
“…Cholesterol sulfate has been noted to inhibit the pancreatic serine proteases trypsin and chymotrypsin (103,104) as well as a yeast pronase (103); it also inhibits pancreatic elastase (105) and DNase I (106). The physiologic significance of these in vitro findings, however, is not fully appreciated.…”
Section: Enzyme Systemsmentioning
confidence: 99%
“…Cholesterol sulfate has been noted to inhibit the pancreatic serine proteases trypsin and chymotrypsin (103,104) as well as a yeast pronase (103); it also inhibits pancreatic elastase (105) and DNase I (106). The physiologic significance of these in vitro findings, however, is not fully appreciated.…”
Section: Enzyme Systemsmentioning
confidence: 99%
“…It was proposed that since CSO 4 has trypsin and chymotrypsin inhibitory properties in vitro, it might thereby affect breakdown of desmosomes, thus causing retention hyperkeratoses and abnormal scaling (18). The strong charge of its sulfate moiety conferring mild detergent properties to CSO 4 was shown to interfere with spontaneous sheet-formation of epidermal lipids in vivo and thus theorized to affect epidermal barrier function by deranging skin lipid layers, repressing cholesterol synthesis, and replacing cholesterol in the lipid sheets (16).…”
Section: Effect Of Slv Content Of Cso 4 On -Hydroxyceramidementioning
confidence: 99%
“…Thus it was theorized that CSO 4 affects epidermal barrier function both by deranging skin lipid layers and by replacing cholesterol in the lipid sheets (16). In another study, it was proposed that since CSO 4 has trypsin and chymotrypsin inhibitory properties in vitro, it might thereby affect breakdown of desmosomes, thus causing retention hyperkeratosis and abnormal scaling (18). Finally, more recently, it was demonstrated that CSO 4 can induce TGase 1 expression in cultured keratinocytes (19), but the connection between excess TGase expression and disease etiology remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CS is a component of cell membranes where it has a stabilizing role and is abundant in the human body with many physiological characteristics 26 . Although CS is already known to inhibit various human proteases [27][28][29][30] and DNase I…”
Section: Discussionmentioning
confidence: 99%